2015
DOI: 10.2217/mmt.15.9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy in Melanoma Patients: A Single Institution Experience

Abstract: The favorable outcome obtained in the present study demonstrates that ECT is a reliable, easy, fast and effective procedure showing benefits in terms of curative and palliative treatment for unresectable cutaneous lesions respecting the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Six of them were excluded from the final analysis for the following reasons: one letter to editor, one case report, one with no data on tumor response, one without separated data on ECT, one reporting on the same patients population of a more recent study by the same authors, and one reporting on primary MM. Seven studies had a retrospective design [16][17][18][19][20][21][22], ten were prospective [11,12,[23][24][25][26][27][28][29][30] and one was a retrospective-prospective analysis [31]. Six studies were published before ESOPE guidelines were issued in 2006 [16-18, 23, 24, 26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of them were excluded from the final analysis for the following reasons: one letter to editor, one case report, one with no data on tumor response, one without separated data on ECT, one reporting on the same patients population of a more recent study by the same authors, and one reporting on primary MM. Seven studies had a retrospective design [16][17][18][19][20][21][22], ten were prospective [11,12,[23][24][25][26][27][28][29][30] and one was a retrospective-prospective analysis [31]. Six studies were published before ESOPE guidelines were issued in 2006 [16-18, 23, 24, 26].…”
Section: Resultsmentioning
confidence: 99%
“…Most lesions were in the trunk and extremities. The size of the treated metastases was reported heterogeneously: some authors reported the volume [11,16,23,24], others the diameter [12,18,19,21,[25][26][27][28][29][30], while four papers did not describe this data [17,20,22,31]. Looking at the diameter, the range was 2-260 mm.…”
Section: Patients and Tumors Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local treatments include surgical resection, electro-chemotherapy (ECT), ablative, topical and intralesional therapies. [11][12][13] Regional treatment options include regional radiation therapy 14 and locoregional chemotherapy by hyperthermic isolated limb perfusion (HILP) or isolated limb infusion (ILI) for locoregional melanoma metastases located in the limbs, 1 or hypoxic pelvic and limb perfusion (HPLP) for cases of synchronous inferior limb and inguinal region and/or pelvic involvement. 15 Systemic treatments, currently proposed for locoregional metastases judged to be unresectable for technical or clinical reasons, include single or combinations of agents with local and/or regional treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with stage III and IV CM with pelvic locoregional metastases, specialist melanoma centres provide local, regional, and systemic treatment options. Local treatments include surgical resection [4], topical therapy with diphencyprone or imiquimod [5], diathermy-fulguration, cryotherapy, laser ablation, radiofrequency ablation, intralesional injection with Rose Bengal [6] or Talimogene laherparepvec [7] or Darumon or Guadagni et al BMC Res Notes (2020) 13:176 Coxsackie Virus A-21, and electro-chemotherapy [8,9]. Regional treatment options include regional radiation therapy [10,11] and hypoxic pelvic perfusion (HPP), as isolated limb perfusion and isolated limb infusion are not anatomically practical for metastases targeting.…”
Section: Introductionmentioning
confidence: 99%